Pengakuan Petrus Dan Tomas Tentang Yesus Sebagai Tuhan: Fondasi Teologis bagi Iman Jemaat di Tengah Pluralisme Agama - Tobing, Jhon Piter; Yusup Amasia Mayopu (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2025)
In the increasingly complex context of religious pluralism, a firm confession of faith in the divinity of Jesus is the primary foundation for the life of the Christian congregation. This study aims to examine the theological meaning of Peter's (Matthew 16:16) and Thomas' (John 20:28) confession of Jesus as Lord, and its relevance for strengthening the congregation's faith amidst the reality of religious diversity. Using a theological-biblical approach and qualitative-descriptive methods, this study explores how the two disciples' statements of faith reflect the core of New Testament Christology and serve as the basis for the church's confessions of faith throughout history. The results of the study indicate that Peter's confession as "the Messiah, the Son of the living God" and Thomas's exclamation "My Lord and my God" are not merely personal statements, but rather universal and normative statements of faith. In the context of religious pluralism, these confessions strengthen the identity of the Christian faith and serve as the basis for open dialogue while remaining faithful to the truth of the Gospel. Therefore, a deep understanding of these confessions is crucial for strengthening the congregation's faith so that it does not drift amidst the relativism of truth that develops in a pluralistic society. This research makes a new contribution by linking the confession of Jesus' two main disciples as a relevant theological foundation in the context of contemporary religious pluralism, which has not been studied in depth in contextual Christology studies in Indonesia.